Using support groups to improve behaviour - Mowat, Joan (Paul Chapman, 2007)
Based on material that has been successfully tried and tested, this book provides an example of a whole school approach to setting up and managing support groups to improve the behaviour of pupils with social, emotional and behavioural difficulties. Suitable for both primary and secondary schools, the strategies in the book align with the aims of the new Primary National Strategy and Key Stage 3 Strategy on behaviour and attendance, as well as the SEAL (Social and Emotional Aspects of Learning) curriculum, the Scottish 'Curriculum for Excellence' and 'Happy, safe and achieving their potential'